Validation of PHASE for deriving N-acetyltransferase 2 haplotypes in the Western Cape mixed ancestry population - Celeste Swart; Surita Meldau; Chad M. Centner; Adrian D. Marais; Fierdoz Omar (African Journal of Laboratory Medicine, 2020)
Background: There is a shortage of data on the accuracy of statistical methods for the prediction of N-acetyltransferase 2 (NAT2) haplotypes in the mixed ancestry population of the Western Cape.